SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT CV. JUNINDO PRATAMA - Ali Mulyawan; Dadi Rosadi; Dianawati Dianawati (STMIK Mardira Indonesia, Bandung, 2019)
This research aims to design customer relationship management information systems that facilitate work to manage service data, complaints, and payments.Customer relationship management support a company to provide customer service in real time by establishing valuable relationships with each customer through the use of information about customers.System analysis uses object-oriented methods with based OOSE (Object Oriented Software Engineeringi).System design using web programming language with framework codeigniter uses MySQL database and web view on android studio.Implementation and testing system is the application system that will be applied and then will be tested using blackbox method.Based on research conclusions about customer relationship management information systems, the admin can already see the latest data consumers make service to the system easily, consumers can already file complaints on the system, consumers can upload proof of payment on the system, consumers can see the service schedule, the owner has can see data service and admin and consumers can communicate with each other using messages in the system. Suggestions based on research on customer relationship management information systems, namely the message menu should be changed with a better display and change the password menu plus the old password column. Keyword : information systems, OOSE (Object Oriented Software Engineeringi), framework codeigniter, MySQL database, android studioDOI : http://doi.org/10.5281/zenodo.3625321